Infection Rate in the Population of Ticks Hyalomma marginatum in the Territory of the Crimean Hemorrhagic Fever (CHF) Natural Focus and Assessment of the Link with the CHF Incidence in the Stavropol Region - N. V. Tsapko (Проблемы особо опасных инфекций, 2021)
Objective of the study was to assess the infection rate in the population of the main CCHF virus vector Hyalomma marginatum and its impact on the CHF incidence in the Stavropol Region.Materials and methods. The data on spontaneous infection of H. marginatum ticks in the territory of the CHF natural focus in the Stavropol Region for the period 2012–2018 are presented. In total, more than 22.000 H. marginatum specimens pooled in 1546 samples were tested. The indication of CCHF virus was performed by PCR method using the reagent set for detecting RNA of the CCHF virus “AmplySens® CCHFV-FL” (produced by Central Research Institute of Epidemiology, Russia). To determine the individual infection rate in pools Beklemishev`s method was used. The data on CCHF incidence and amount of tick-bitten persons are taken from official statistics and Annual Epidemiological Report on CHF Incidence provided by the Rospotrebnadzor Administration in the Stavropol Region for the period of 2012–2018.Results and discussion. RNA of CCHF virus was detected in 161 (10.4 %) out of 1546 pooled ticks. The highest infection rate (20 %) was among nymphs. The infection rate for pooled males of H. marginatum was 11 % and for females – 8.5 %. Circulation of Crimean-Congo hemorrhagic fever virus is confirmed in major part of the Stavropol Region. The average infection rate among H. marginatum population was 1.54 % for the period of 2012–2018, ranging from 0.23 % in 2014 to 2.97 % in 2017. It is established that the level of infection rate among H. marginatum population does not affect the CHF incidence in the Stavropol Region. Probably it is not the number of infected ticks in the population that determines the CHF incidence rate but their abundance.